(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This article focuses on improving the speed-strength qualities of adolescent short-distance runners in athletics. It analyzes scientifically based training load methods to enhance athletes’ running performance. The study examines the effect of weightlifting exercises on the speed-strength abilities of adolescents, and appropriate training loads are developed for training programs.The main purpose of the article is to improve the physical fitness of young athletes and to provide practical recommendations for direct load-based individual and group training aimed at recovery. The results show that special exercises significantly improve athletes’ explosive technique, which contributes to their overall performance. The study also presents methodological approaches for optimally organizing the training process, taking into account the physiological characteristics of adolescents.